COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN BULO WATTANG VILLAGE PANCA RIJANG DISTRICT SIDENRENG RAPPANG REGENCY - Janna, Miftahul; Ramadhan, Muhammad Rohady; Barisan, Barisan (Gema Kampus IISIP YAPIS Biak, 2025)
This study aims to analyze the level of community participation in the development planning of Bulo Wattang Village and identify the factors that affect it. The research uses a quantitative method with data collection techniques through observation, questionnaires, and literature studies. The research sample of 94 respondents was determined by the Slovin formula. Data analysis was carried out descriptively and using simple linear regression. The results showed that the level of community participation was in the medium category with low details of information, high consultation, moderate collaboration, and fairly good implementation. The regression test showed that community participation had a significant effect on development planning with values of R = 0.704 and R² = 0.496. This study recommends increasing information transparency, strengthening education, and providing inclusive participation spaces to realize effective and sustainable development planning.